2010
DOI: 10.1021/bc900553n
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Evaluation of a Robust, Biodegradable Dendrimer

Abstract: PEGylated dendrimers are attractive for biological applications due to their tunable pharmacokinetics and ability to carry multiple copies of bioactive molecules. The rapid and efficient synthesis of a robust and biodegradable PEGylated dendrimer based on a polyester-polyamide hybrid core is described. The architecture is designed to avoid destructive side-reactions during dendrimer preparation while maintaining biodegradability. Therefore, a dendrimer functionalized with doxorubicin (Dox) was prepared from co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(101 citation statements)
references
References 50 publications
2
99
0
Order By: Relevance
“…Also, there are preclinical promising in vitro and in vivo results with active targeting dendrimers [73,365], for example antibody-dendrimer conjugates showed better efficacy than free antibodies [380][381][382][383], peptide (RGD) dendrimer conjugates showed enhanced tumor targeting [384][385][386], and folic acid functionalized dendrimers generated better tumor accumulations than untargeted controls or free drug, producing a stronger reduction of the tumor size [73,[387][388][389][390]. The slow translation of these preclinical studies to clinical trials may be due to the current toxicity of dendrimers [391,392], with the aim of the current research in the development of new biocompatible and less toxic alternatives [367,[393][394][395][396][397][398][399].…”
Section: Polymeric Nanocarriersmentioning
confidence: 99%
“…Also, there are preclinical promising in vitro and in vivo results with active targeting dendrimers [73,365], for example antibody-dendrimer conjugates showed better efficacy than free antibodies [380][381][382][383], peptide (RGD) dendrimer conjugates showed enhanced tumor targeting [384][385][386], and folic acid functionalized dendrimers generated better tumor accumulations than untargeted controls or free drug, producing a stronger reduction of the tumor size [73,[387][388][389][390]. The slow translation of these preclinical studies to clinical trials may be due to the current toxicity of dendrimers [391,392], with the aim of the current research in the development of new biocompatible and less toxic alternatives [367,[393][394][395][396][397][398][399].…”
Section: Polymeric Nanocarriersmentioning
confidence: 99%
“…To minimize the hydrolytic susceptibility of the ester bond during synthesis of drug conjugates, Fréchet, Szoka and coworkers reported an elegant synthesis that combines the biocompatibility of bis-HMPA dendrimers with the robustness of polyamide dendrimers, yielding a hybrid scaffold capable of translation into clinical studies [98]. A drug loaded PEGylated ester-amide dendrimer is shown in Figure 8.…”
Section: Methodsmentioning
confidence: 99%
“…Conventionally, nanoscale therapeutics is derived from polymer-drug conjugates, in which a drug is covalently bound through cleavable linkages such as the pH sensitive cis-aconityl, hydrazine, and acetal linkages [56,[90][91][92][93][94][95][96][97][98]. On the other hand, supramolecular drug delivery systems based on block copolymer micelles or dendritic systems have shown great promise and utility for tumor targeting and drug delivery [8,19,[99][100][101][102][103].…”
Section: Covalent and Non-covalent Dendrimer-drug Systemsmentioning
confidence: 99%
“…Li et al (56) investigated a synthetic vector system based on PAMAM dendrimers for effective delivery of survivin antisense oligonucleotide into transplanted colorectal tumor cells to reduce the expression of survivin and inhibit the growth of subcutaneously transplanted colorectal cancer in nude mice. PAMAMs have also been utilized in synthetic drug delivery vehicles due to their properties, such as high loading content, simple synthesis, excellent biodegradability and remarkable versatility (57). Drugs covalently bound to the periphery or loaded into the inner core of a dendrimer are efficiently delivered to the site of action (58,59).…”
Section: Dendrimersmentioning
confidence: 99%
“…PEGylated dendrimers have also shown great promise as drug carriers; they are manufactured in an easy and cost-effective manner, but exhibit higher targeting and anticancer abilities, as van der Poll et al (57) demonstrated in their in vivo study.…”
Section: Dendrimersmentioning
confidence: 99%